Samizdat, tamizdat, and beyond : transnational media during and after socialism - Kind-Kovács, Friederike 1978- HerausgeberIn; Labov, Jessie HerausgeberIn (Studies in contemporary European history, 2013)
Introduction -- Producing and circulating samizdat/tamizdat before 1989. Ardis facsimile and reprint editions: giving back Russian literature / Ann Komaromi -- The Baltic connection: transnational networks of resistance after 1976 / Fredrik Lars Stöcker -- Radio Free Europe and Radio Liberty as the "echo chamber" of tamizdat / Friederike Kind-Kovács -- Contact beyond borders and historical problems: kultura, Russian emigration and the Polish opposition / Karolina Ziolo-Puzuk -- Diffusing non-conformist ideas through samizdat/tamizdat before 1989. "Free conversations in an occupied country": cultural transfer, social networking and political dissent in Romanian tamizdat / Cristina Petrescu -- The danger of over-interpreting dissident writing in the West: Communist terror in Czechoslovakia, 1948-1968 / Muriel Blaive -- Renaissance or reconstruction? intellectual transfer of civil society discourses between Eastern and Western Europe / Agnes Arndt -- Transforming modes and practices of alternative culture. The bards of Magnitizdat: an aesthetic political history of Russian underground recordings / Bian A. Horne -- Writing about apparently non-existent art: the tamizdat journal A-Ja and Russian unofficial arts in the 1970s-1980s / Valentina Parisi -- "Video knows no borders": samizdat television and the unofficial public sphere in "normalized" Czechoslovakia / Alice Lovejoy -- Moving from samizdat/tamizdat to alternative media today. Postprintium? digital literary samizdat on the Russian Internet / Henrike Schmidt -- Independent media, transnational borders, and networks of resistance: collaborative art radio between Belgrade (Radio B92) and Vienna (ORF) / Daniel Gilfillan -- "From wallpapers to blogs": samizdat and Internet in China / Martin Hala -- Reflections on the revolutions in Europe: lessons for the Middle East and the Arab Spring / Barbara J. Falk